Molecular Mechanisms of Ca2+ Signaling in Neurons Induced by the S100A4 Protein - Darya Kiryushko; Vera Novitskaya; Vladislav Soroka; Jörg Klingelhöfer; Eugene Lukanidin; Vladimir Berezin; Elisabeth Bock (2006)
The S100A4 protein belongs to the S100 family of vertebrate-specific proteins possessing both intra- and extracellular functions. In the nervous system, high levels of S100A4 expression are observed at sites of neurogenesis and lesions, suggesting a role of the protein in neuronal plasticity. Extracellular oligomeric S100A4 is a potent promoter of neurite outgrowth and survival from cultured primary neurons; however, the molecular mechanism of this effect has not been established. Here we demonstrate that oligomeric S100A4 increases the intracellular calcium concentration in primary neurons. We present evidence that both S100A4-induced Ca2+ signaling and neurite extension require activation of a cascade including a heterotrimeric G protein(s), phosphoinositide-specific phospholipase C, and diacylglycerol-lipase, resulting in Ca2+ entry via nonselective cation channels and via T- and L-type voltage-gated Ca2+ channels. We demonstrate that S100A4-induced neurite outgrowth is not mediated by the receptor for advanced glycation end products, a known target for other extracellular S100 proteins. However, S100A4-induced signaling depends on interactions with heparan sulfate proteoglycans at the cell surface. Thus, glycosaminoglycans may act as coreceptors of S100 proteins in neurons. This may provide a mechanism by which S100 proteins could locally regulate neuronal plasticity in connection with brain lesions and neurological disorders.